If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(n + -2) + 9 = 5n + 3 Reorder the terms: 4(-2 + n) + 9 = 5n + 3 (-2 * 4 + n * 4) + 9 = 5n + 3 (-8 + 4n) + 9 = 5n + 3 Reorder the terms: -8 + 9 + 4n = 5n + 3 Combine like terms: -8 + 9 = 1 1 + 4n = 5n + 3 Reorder the terms: 1 + 4n = 3 + 5n Solving 1 + 4n = 3 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. 1 + 4n + -5n = 3 + 5n + -5n Combine like terms: 4n + -5n = -1n 1 + -1n = 3 + 5n + -5n Combine like terms: 5n + -5n = 0 1 + -1n = 3 + 0 1 + -1n = 3 Add '-1' to each side of the equation. 1 + -1 + -1n = 3 + -1 Combine like terms: 1 + -1 = 0 0 + -1n = 3 + -1 -1n = 3 + -1 Combine like terms: 3 + -1 = 2 -1n = 2 Divide each side by '-1'. n = -2 Simplifying n = -2
| 4x+y+3x-2y=180 | | 4+5(2x+4)=6x | | x/2+7=13 | | 4(1/4x-2)=0 | | 100-x=x+60 | | 7x+6(-3x+11)=154 | | -16+24y+19y+30y=-22y-16 | | (xy^5z^3)(x^3y^3z)= | | 4secantx+8=0 | | x/4+6=14 | | log^4(5x-8)=4 | | -3-12=-5+c | | 2.3X+4.5=.3-5X | | 13w^2-38w+25=0 | | 18/8 | | 27y=13y+22-19y+9y | | 4+5(2x+4)-6x= | | 6a-96=0 | | 4+5(2x+4)-6x=28 | | v=rh | | 2p+5=3(1p-6) | | 2x^2-6x-36= | | 4x-3x+x= | | 6=3y-12 | | 29z=-7z-9-25+14z | | 234+234= | | 4x-3x-x= | | 2/3(4x-1)=22 | | (12y^2+17y-4)+(9y^2-13y+3)= | | -7y/8+8/8=-8y/5-9/5+2y/3 | | 4(7-3x)=1/16 | | 11/6+z+2z=4z/7 |